Green Manufacturing and CSR in Enhancing Firm Performance: The Mediating Role of Firm Reputation - Jesika, Naomi; Putri, Fitria Rachmawati (Research Horizon, 2025)
This study aims to examine the effect of green manufacturing and Corporate Social Responsibility (CSR) on company performance, with company reputation as a mediating variable. The theoretical basis used is the Natural Resource-Based View (NRBV), which states that resources and capabilities oriented towards sustainability can be the basis for long-term competitive advantage. Data were collected through a survey of manufacturing companies in Central Java Province that have implemented Life Cycle Assessment (LCA). The analysis was conducted using Structural Equation Modeling (SEM) to test the direct and indirect effects between variables. The results showed that green manufacturing and CSR had a significant effect on company reputation, which in turn had a positive effect on company performance. In addition, green manufacturing and CSR were also proven to have a direct effect on performance, although the mediating role of company reputation was not statistically significant. These findings emphasize the importance of reputation as a strategic intangible asset, but its effectiveness as a mediator can vary depending on the organizational context. This study recommends a broader application of environmental and social strategies, and encourages further research with a wider sample size and mediating variables.